Advancing Psychological Interventions to Combat Mental Health Stigma and Foster Community Resilience in the Philippines: A Culturally-Informed Framework for Social Development - Hu, Yue (International Journal of Public Health and Medical Research, 2025)
This study explores mental health stigma in the Philippines and proposes a culturally-informed psychological framework to improve community resilience and intervention effectiveness. Using both qualitative and quantitative methods, it examines how cultural concepts such as hiya (shame), spiritual beliefs, and social norms shape attitudes toward mental illness and help-seeking. The research highlights the limitations of current systems despite the passage of the Mental Health Act of 2018 and offers recommendations for more accessible, culturally sensitive, and sustainable community-based mental health services. The findings underscore the importance of resilience in reducing stigma and promoting long-term social development.